2008
DOI: 10.2139/ssrn.1295353
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Dynamics and Speculation: A Multivariate Financial Approach

Abstract: This paper assesses empirically whether speculation affects oil price dynamics. The growing presence of financial operators in the oil markets has led to the diffusion of trading techniques based on extrapolative expectations. Strategies of this kind foster feedback trading that may cause large departures of prices from their fundamental values. We investigate this hypothesis using a modified CAPM that follows Shiller (1984) and Sentana and Wadhwani (1992). At first, a univariate GARCH(1,1)-M is estimated assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 22 publications
6
58
0
1
Order By: Relevance
“…Park and Ratti [2008] use a VAR model. Many authors use the family of GARCH models, specifically bivariate GARCH [Cifarelli, Paladino 2010;Arouri, Lahiani, Nguyen 2011;Arouri 2011;Papież, Śmiech 2012], generalised VAR-GARCH [Arouri, Jouini, Nguyen 2012;Mensi et al 2013] and multivariate GARCH (Creti et al (2013) use dynamic conditional correlation (DCC) GARCH).…”
Section: Causality In Distribution Between European Stock Markets Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Park and Ratti [2008] use a VAR model. Many authors use the family of GARCH models, specifically bivariate GARCH [Cifarelli, Paladino 2010;Arouri, Lahiani, Nguyen 2011;Arouri 2011;Papież, Śmiech 2012], generalised VAR-GARCH [Arouri, Jouini, Nguyen 2012;Mensi et al 2013] and multivariate GARCH (Creti et al (2013) use dynamic conditional correlation (DCC) GARCH).…”
Section: Causality In Distribution Between European Stock Markets Andmentioning
confidence: 99%
“…Existing studies present different results; some find that there is no significant effect of oil price shocks on stock prices [Cong et al 2008;Hammoudeh, Choi 2006;Mohanty, Nandha, Bota 2010;Maghyereh 2004;Sari, Soytas 2006], others find a significant positive impact of oil prices on stock prices [Narayan, Narayan 2010;Nguyen, Bhatti 2012;Broadstock, Cao, Zhang 2012;Mohanty et al 2011], while still others find a significant negative effect [Aloui, Jammazi 2009;Park, Ratti 2008;Cifarelli, Paladino 2010]. Hence, the evidence from the existing literature on the significance and sign of the impact of oil price changes on stock prices is still inconclusive.…”
Section: Causality In Distribution Between European Stock Markets Andmentioning
confidence: 99%
“…The evidence on the effects of speculation is mixed. In some studies, speculation is shown to have a statistically significant effect on price and volatility in oil markets, particularly in the lead up to the historically high oil prices achieved pre-crisis (Sornette et al, 2009, Kaufmann and Ullman, 2009, Cifarelli and Paladino, 2010, Du et al, 2011. In contrast, Büyüksahin and Harris (2011) find no evidence that non-commercial positions, including hedge fund positions, have a causal effect on oil prices.…”
Section: Introductionmentioning
confidence: 99%
“…Among several financial factors, speculative expectation has been indicated as an important determinant of the price for a commodity [18]. Studies have also provided support for the role of speculation in the oil market, especially for its role in the rise of crude oil prices [18,[28][29][30]. However, the role of speculation in causing the significant changes in oil prices is still debatable.…”
Section: Introductionmentioning
confidence: 99%